2013
DOI: 10.1007/s12041-013-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection reveals effects of interaction between high-molecular-weight glutenin subunits and waxy alleles on dough-mixing properties in common wheat

Abstract: The glutenin and waxy loci of wheat are important determinants of dough quality. This study was conducted to evaluate the effects of high-molecular-weight glutenin (HMW-GS) and waxy alleles on dough-mixing properties. Molecular mapping was used to investigate these effects on Mixograph properties in a population of 290 (Nuomai1 x Gaocheng8901) recombinant inbred lines (RILs) from three environments in the harvest years 2008, 2009 and 2011. The results indicated the following: (i) the Glu-A1 and Glu-D1 loci hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Although 119 additive QTLs were detected for dough rheological and starch pasting properties, 50 of them were grouped into 11 clusters. QTL clusters for dough strength on chromosomes 1AL, 1BL, and 1DL detected in the present study were associated with HMW-GSs, consistent with previous reports (Huang et al, 2006 ; Deng et al, 2013 ). The interval 24.9–34.2 cM on chromosome 2BS is a QTL cluster impacting MPT, MTxW, WA, ST and C2, which coincides with their significant phenotypic correlations.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although 119 additive QTLs were detected for dough rheological and starch pasting properties, 50 of them were grouped into 11 clusters. QTL clusters for dough strength on chromosomes 1AL, 1BL, and 1DL detected in the present study were associated with HMW-GSs, consistent with previous reports (Huang et al, 2006 ; Deng et al, 2013 ). The interval 24.9–34.2 cM on chromosome 2BS is a QTL cluster impacting MPT, MTxW, WA, ST and C2, which coincides with their significant phenotypic correlations.…”
Section: Discussionsupporting
confidence: 93%
“…A similar co-localized region for dough development time, stability and softening was also located on chromosome 2B (Maphosa et al, 2015 ). A QTL cluster for MPV, MPW and PTI between BS00072151_51 and GENE-1617_131 , positioned in the interval of 61.3–81.9 cM on chromosome 3B, is likely to be in the same region for MPT, MPI, and MTxW reported by Deng et al ( 2013 ). Another QTL cluster for MPT, MTxW, DT, ST, C2, and C3 identified in the interval 35.8–63.1 cM on chromosome 4B, is likely the same as a QTL cluster for Mixograph midline peak time, midline tail width, envelope peak energy and envelope peak time (Patil et al, 2009 ).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Conti et al (2011) identified 3 QTLs on chromosome 1A. Deng et al (2013) indicated that the Glu-A1 locus has greater impacts on mixograph properties associated with dough mixing. Jin et al (2016) reported many QTLs linked with Glu-A1-HMW for the mixograph midline peak value, midline peak width, and mixograph development time, and the most important QTLs causing significant variations in the studied traits were located on chromosomes 1BL, 6AL, 6BL, and 7AS.…”
Section: Discussionmentioning
confidence: 99%